Analisis Pendapatan Usahatani Tanaman Hortikultura di Food Estate Humbang Hasundutan (Jurnal Agribisnis Indonesia, 2024)
Food functions as a pillar of national development and plays a role in maintaining a country’s economic, social and political stability of a country, all of which must be fulfilled by the state. Many countries are facing global food problems, leading to significant increases in commodity prices. The Indonesian government launched a National food storage developments strategy to overcome the food crisis. The "Food estate" program aims to ensure that high-quality food is available, accessible and consumed by the public, and to increase domestic production. In North Sumatra, efforts to increase food security through the food estate program are considered the right solution. 215 hectares of land was converted into a horticultural area in Humbang Hasundutan Regency. Horticultural crops developed in the Humbang Hasundutan Regency food estate include potatoes, shallots, garlic and tomatoes. This research aim is to analyze the income from farming horticultural crops in the Humbang Hasundutan food estate. This research data analysis uses farming income analysis. The analysis results show that the largest total income (income) from farming is the potato plant, amounting to Rp. 371.184.000,00. The conclusion of this research is that of the 4 commodities, only 1 commodity made a profit, while the income of the other three commodities received a minus income value.